Diseño de Antenas Yagi Uda Usando Algoritmos Genéticos - Gómez, Juan Carlos; Barrero Páez, Luis; Celelita, Ricardo (Ingeniería, 2002)
This paper presents a design method, based on genetic algorithms, to obtain antennas Yagi Uda of characteristic electric good. This method adjusts the physical dimensions of the array (longitude of the elements and separation among them), to obtain an antenna Yagi Uda composed by elements of different longitude and spaced not evenly, with the purpose of maximizing the directividad of the arrangement, and to complete requirements as for input impedance, Front to Back Ratio, and Side Lobe Level. Also, three antennas Yagi Uda is presented designed by this method, and they are compared with the results for equally spaced arrangements designed by several authors.